Generalized implicit solution of ITZ percolation threshold and its effect on the diffusivity of concrete: Influence of aggregate shape- and size-polydispersities. (January 2023) - Li, Mingqi; Chen, Huisu; Qing, Longbang; Lin, Jianjun
Highlights: A generalized implicit solution is developed to capture the ITZ percolation threshold. ITZ percolation threshold of concretes including poly-shaped aggregates are obtained. Coupling effect of aggregate shape- and size-polydispersities on ITZ percolation is suited. Influence of aggregate shape- and size-polydispersities on diffusivity is investigated. Abstract: Concrete is usually assumed to be a three-phase particulate composite composed of aggregate, cement paste and interfacial transition zone (ITZ) around the aggregate. Due to the high porosity of the ITZ, the transport of aggressive media in the ITZ is more rapid than that in the cement paste. However, it is still unclear how concrete components, like ITZ thickness and aggregate shape- and size-polydispersities affect the ITZ percolation threshold. This paper develops a generalized implicit solution to establish the quantitative relationship between the ITZ percolation threshold and concrete components using an analogy between lattice and continuum percolation. The reliability of the generalized implicit solution is confirmed by comparing the theoretically calculated ITZ percolation thresholds with the numerical results in this work and other literature. The concrete diffusivity is also predicted by combining the obtained ITZ percolation threshold with the differential effective medium approximation and the multi-component percolation-based effective medium model. Graphical abstract: Image, graphical abstract